Analysis of a near field MIMO wireless channel using 5.6 GHz dipole antennas - Maricar, Mohamed Ismaeel; Gradoni, Gabriele; Greedy, Steve; Ivrlac, Michel T.; Nossek, Josef A.; Phang, Sendy; Creagh, Stephen C.; Tanner, Gregor; Thomas, David W.P. (2016)
Understanding the impact of interference upon the performance of a multiple input multiple output (MIMO) based device is of paramount importance in ensuring a design is both resilient and robust. In this work the effect of element-element interference in the creation of multiple channels of a wireless link approaching the near-field regime is studied. The elements of the 2-antenna transmit- and receive-arrays are chosen to be identical folded dipole antennas operating at 5.6 GHz. We find that two equally strong channels can be created even if the antennas interact at sub-wavelength distances, thus confirming previous theoretical predictions.